Рrevention of contrast-induced nephropathy during interventional treatment of acute coronary syndrome - L.O. Miakinkova; T.I. Yarmola; G.L. Pustovoit; Iu.A. Kostrikova; B.O. Pysana; V.V. Talash (Medičnì Perspektivi, 2023)
The aim of the work was to determine the risk factors of contrast-induced nephropathy in patients with acute coronary syndrome and to evaluate the effectiveness of methods of its prevention. There were examined 62 patients admitted to the interventional cardiology department during 9 months of routine practice with a diagnosis of acute coronary syndrome and concomitant chronic kidney disease. Among them, 56.45% have diabetic nephropathy, 21% – hypertensive nephropathy, 19.35% – chronic pyelonephritis, 3.2% – gouty nephropathy. According to the stages of chronic kidney disease: I stage – 8.1%, II stage – 46.8%, III A stage – 30.6%, III B stage – 14.5% of patients. The control group consisted of 32 patients with acute coronary syndrome without kidney pathology. All patients underwent urgent percutaneous coronary intervention with a water-soluble low-osmolarity radiocontrast medium. The risk of contrast-induced nephropathy was determined according to the Mehran scale. Contrast-induced nephropathy was diagnosed by an increase in serum creatinine by >25% over 24-48 hours. Prevention of contrast-induced nephropathy according to existing recommendations was carried out by prescribing early statin therapy and diuresis-controlled combined hydration in 22 patients with concomitant chronic kidney disease. Mathematical processing was performed using Statistica 8.0 software (StatSoft Inc, USA). Patients with chronic kidney disease had a high and very high risk of contrast-induced nephropathy in 19.4% and 3.2% of cases, among them in 91.6% high, and in 100% – very high-risk contrast-induced nephropathy developed. Patients in the control group had a low to moderate risk, none of them developed contrast-induced nephropathy. It has been shown that the risk of contrast-induced nephropathy depends on the stage of chronic kidney disease and is associated with a decrease in the ejection fraction of the left ventricle (≤40%), acute left ventricle failure of the III and IV classes according to Killip, a decrease in diuresis up to ≤0.6 ml/h/kg in the first 12-24 hours after urgent percutaneous coronary intervention; taking metformin 6-12 hours before the administration of the X-ray contrast medium and the glomerular filtration rate ≤45 ml/min./1.73 m2. In patients who underwent prevention of contrast-induced nephropathy in its entirety, its development was not registered.